Germinação e morfologia da semente e plântula de mogno (swietenia macrophyla, king) - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1996)
Mahogany (Swietenia macrophylla, King) belongs to the Meliaceae family, naturally occurring from the Yucatán Peninsula to Colombia, Venezuela, Peru and the Amazon region, is threatened with extinction due to its great utility in the construction of luxury furniture, ornaments, etc. The objective of this work is to study the germination of mahogany in different substrates and to make morphological descriptions of the fruit, seed and seedling, analyzing also the height and diameter of the epicotyl. The experiment was entirely randomized with 4 treatments and 4 repetitions that consisted of: IT-Sand + poultry litter (3:1), T2-Sand + carbonized rice husk (1:1); T3-Sand + carbonized rice husk (1.5:3); T4-Black earth + carbonized rice husk (1: 1). The best result for germination was T2 treatment followed by T3 while for height and epicotyl diameter there was no significant difference at 5% probability level. Germination started 11 days after planting, characterized as cryptocotyledonary, hypogeal. The dry fruit is a brown, septate capsule. The seed coat is winged and shiny brown; without this coat the seed measures 16-251 mm long, 8-101 mm wide, and 3-4 mm thick. At 5 days after emergence the roots measure 95mm long, with numerous radicels. The leaves are simple, petiolate, glabrous, with pulvines at the base, lanceolate-ovate, alternate or opposite only in the first pair. The species Swietenia macrophylla has great potential for reforestation work since its germination is fast and is one of the species threatened with extinction.
Germination and morphology of seed and seedling of mahogany (swietenia macrophyla, king)
Keywords: Swietenia macrophyla, king; Mogno; Meliaceae; Germinação; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL